Nonlinear differential equations with asymptotically stable solutions - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions of asymptotic stability of all solutions of the equation \(dx dt = A(x)x\) , t≥0in a Banach space E in the case where σ(A(x)⊂λ:Reλ